Critical care MCQs a companion for intensive care exams - Lobaz, Steven; Hamilton, Mika; Glossop, Alastair J.; Raithatha, Ajay (Tfm Publishing, 2015)
Critical Care MCQs is the perfect companion for anyone sitting exams in intensive care, as a training resource or just wanting to improve their knowledge in this constantly developing area of medical practice.This book leads the reader through 450 true/false questions with referenced explanations, covering core syllabus topics and key influential papers to date.